The philosophy of science : science and objectivity - Couvalis, George, 1953- (Sage Publications, 1997)
This comprehensive textbook provides a clear nontechnical introduction to the philosophy of science. Through asking whether science can provide us with objective knowledge of the world, the book provides a thorough and accessible guide to the key thinkers and debates that define the field. George Couvalis surveys traditional themes around theory and observation, induction, probability, falsification and rationality as well as more recent challenges to objectivity including relativistic, feminist and sociological readings. This provides a helpful framework in which to locate the key intellectua.